Correction: Yu et al. Achieving Effective Multimodal Imaging with Rare-Earth Ion-Doped CaF2 Nanoparticles. Pharmaceutics 2022, 14, 840 - Zhenfeng Yu; Yuanyuan He; Timo Schomann; Kefan Wu; Yang Hao; Ernst Suidgeest; Hong Zhang; Christina Eich; Luis J. Cruz (MDPI AG, 2024)
There was an error in the original publication [...]